Krisis Representasi: Analisis 0% Keterwakilan Perempuan dalam DPRD pada Empat Kabupaten di Nusa Tenggara Timur - Ivana Joya Mahadina; Kheysa Husna Khasifa Romadhoni; Ika Arinia Indriyany (Sociale : Journal of Social and Political Sciences, 2026)
Women’s political representation is a key indicator of inclusive democracy; however, the 2024 legislative elections reveal an extreme condition of 0% female representation in several regions of East Nusa Tenggara. This phenomenon reflects a gap between affirmative policies and local political realities. The problem addressed in this study is the complete absence of women in the Regional House of Representatives (DPRD) in four regencies—Lembata, East Flores, Ngada, and Rote Ndao—and the underlying factors contributing to this condition from the perspective of political representation theory. This study employs a qualitative approach using a literature review and document analysis method. Data were collected from academic journals, official government reports, and statistical sources, and analyzed through thematic content analysis using Hanna Pitkin’s theory of representation. The findings indicate that the absence of women constitutes a failure of descriptive representation, as legislative institutions do not reflect the demographic composition of society. Furthermore, this condition weakens substantive representation, particularly in addressing women’s interests in public policy. Key barriers include patriarchal culture, non-inclusive party recruitment mechanisms, and unequal access to political resources. In conclusion, the crisis of women’s representation at the local level is not only caused by weak implementation of affirmative policies but also by gender-biased social and political structures. Comprehensive efforts are required, including political party reform, strengthening women’s political capacity, and transforming political culture to achieve more inclusive democracy.